2019
DOI: 10.3389/fendo.2019.00364
|View full text |Cite
|
Sign up to set email alerts
|

Transient Elastography and Controlled Attenuation Parameter (CAP) in the Assessment of Liver Steatosis in Severe Adult Growth Hormone Deficiency

Abstract: Non-alcoholic fatty liver disease (NAFLD) is common in patients with growth hormone deficiency (GHD). Some noninvasive techniques have been used to quantify liver fat, such as the controlled attenuation parameter (CAP). Objective: To evaluate CAP as a tool to identify liver steatosis and its relationship with different clinical and biochemical metabolic parameters in a group of patients with severe adult growth hormone deficiency (AGHD), and to compare the evolution of metabolic profile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 48 publications
0
12
1
Order By: Relevance
“…The data on effectiveness of GH therapy on NAFLD/NASH in this patient population are limited to a few studies that included a very small number of patients for a duration of treatment only for 6 months (Table 2 ). [ 14 , 15 , 16 , 17 , 18 ] In all studies, treatment was started with a low‐dose rhGH and titrated to normal IGF‐1 level per guidelines recommendations. One demonstrated significant improvement of steatosis and fibrosis in 5 patients with NASH who underwent paired liver biopsies after 6–12 months of treatment with GH.…”
Section: Gh For Treatment Of Nafldmentioning
confidence: 99%
See 1 more Smart Citation
“…The data on effectiveness of GH therapy on NAFLD/NASH in this patient population are limited to a few studies that included a very small number of patients for a duration of treatment only for 6 months (Table 2 ). [ 14 , 15 , 16 , 17 , 18 ] In all studies, treatment was started with a low‐dose rhGH and titrated to normal IGF‐1 level per guidelines recommendations. One demonstrated significant improvement of steatosis and fibrosis in 5 patients with NASH who underwent paired liver biopsies after 6–12 months of treatment with GH.…”
Section: Gh For Treatment Of Nafldmentioning
confidence: 99%
“…[ 11 ] The role of GH therapy for reversal of NAFLD in patients with AGHD is still controversial, with some studies showing beneficial effect (including histologic improvement), [ 14 , 17 ] while others lacking improvement (via nonhistologic measures). [ 16 , 18 ] Interestingly, GH‐releasing hormone analogue had shown robust beneficial effect on NAFLD in patients with human immunodeficiency virus (HIV). [ 19 ]…”
Section: Introductionmentioning
confidence: 99%
“…Transient elastography (TE) is an ultrasound-based modality that simultaneously measures liver steatosis and fibrosis. TE transducer produces a low-frequency (50 Hz) shear wave that propagates through the liver tissue, followed by a pulse-echo ultrasound that measures its velocity, which reflects the degree of liver stiffness or liver stiffness measurement (LSM) [ 33 , 34 , 35 , 36 ]. The controlled attenuation parameter (CAP) estimates the degree of ultrasound attenuation by hepatic fat at the central frequency of transient elastography [ 37 ].…”
Section: Available Imaging Modalities For Liver Fat Assessment Compared To Mrsmentioning
confidence: 99%
“…11 It is known to be associated with an unfavorable lipid pro le, with increased triglycerides, cholesterol, body fat, and liver steatosis, all of which are associated with an increased incidence of vascular disease. 12 A recent study demonstrated that hypopituitary patients without GH replacement have more dyslipidemia, but lower homeostasis model assessment (HOMA-IR) and waist/height values and the occurrence of metabolic syndrome was similar to a control group, paired by age, gender, and Body Mass Index (BMI). 13 Clinical manifestations of Secondary Adrenal Insu ciency are nonspeci c, such as lassitude in the early stage, symptoms frequently attributed to disability related to aging.…”
Section: Introductionmentioning
confidence: 99%